Article Review: Pemanfaatan Insektisida Nabati untuk Pengendalian Wereng Batang Coklat (Nilaparvata lugens Stal.) - Tuti, Harlina Kusuma; Sari, Yulia Padma; Batubara, Junianto S (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Botanical pesticides are pesticides derived from natural plant products that contain bioactive compounds such as secondary compounds. This compound can function as an inhibitor of development, reduces fertility, inhibits appetite (anti-feedant), repellent, attractant, has a direct effect as a poison and prevent and reduce put down the egg. Botanical insecticides are insecticides produced from plant extracts, which are obtained from various parts of plants such as flowers, fruit, seeds, leaves, stems and roots, which contain secondary metabolite compounds. Secondary metabolite compounds produced by plants include essential oils, alkaloids, phenols, flavonoids, tannins, triterpenoids, steroids and saponins. Several lying plants that produce secondary metabolite compounds are good alternatives as a source of raw materials for vegetable insecticides because they are easy to obtain and do not require fertile soil to grow, including: Tinospora crispa (L.) Miers., Azadirachta indica (A.) Juss., Swietenia mahagoni and Annona squamosa.